Использование POWER SHAPE для создания модели временной шины для транспортировки больных с переломом конечностей - Бесарабец, Ю. И. (Видавництво Львівської політехніки, 2012)
У роботі висвітлено основні питання щодо транспортної іммобілізації та зміщення ушкоджених костей при цьому. Це завдання розглянуто на стадії машинного експерименту. Для проведення такого експерименту необхідно створити модель фіксувального обладнання і, використовуючи програму ANSYS, розрахувати можливі зміщення зламаних ділянок костей. The basic questions of a transport immobilization and arising up here displacements of the damaged bones are in-process considered. This task is considered on the stage of machine experiment. For the leadthrough of such experiment it is necessary it was to create the model of fixative device and with the use of the program ANSYS to conduct the calculations of possible displacements of broken-down areas of bones.